The BCG Vaccine for COVID-19: First Verdict and Future Directions - Gonzalez-Perez, Maria; Sanchez-Tarjuelo, Rodrigo; Shor, Boris; Nistal-Villan, Estanislao; Ochando, Jordi (Frontiers in Immunology, 2021)
Despite a rapid development of the vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), it will take several months to have enough doses and the proper infrastructure to vaccinate a good proportion of the world population. In this interim, the accessibility to the Bacille Calmette-Guerin (BCG) may mitigate the pandemic impact in some countries and the BCG vaccine offers significant advantages and flexibility in the way clinical vaccines are administered. BCG vaccination is a highly cost-effective intervention against tuberculosis (TB) and many low-and lower-middle-income countries would likely have the infrastructure, and health care personnel sufficiently familiar with the conventional TB vaccine to mount full-scale efforts to administer novel BCG-based vaccine for COVID-19. This suggests the potential for BCG to overcome future barriers to vaccine roll-out in the countries where health systems are fragile and where the effects of this new coronavirus could be catastrophic. Many studies have reported cross-protective effects of the BCG vaccine towards non-tuberculosis related diseases. Mechanistically, this cross-protective effect of the BCG vaccine can be explained, in part, by trained immunity, a recently discovered program of innate immune memory, which is characterized by non-permanent epigenetic reprogramming of macrophages that leads to increased inflammatory cytokine production and consequently potent immune responses. In this review, we summarize recent work highlighting the potential use of BCG for the treatment respiratory infectious diseases, highlighting the potential use of the BCG vaccine as an adjuvant, to decrease sickness of SARS-CoV-2 infection and/or to mitigate the effects of concurrent respiratory infections.